An early-stage project complexity assessment tool for the AEC industry. Issue 2 (13th August 2021) - Vaz-Serra, Paulo; Edwards, Peter; Aranda-Mena, Guillermo
Abstract : Purpose: Complex projects require careful management. They may expose stakeholders to greater risks and place additional demands upon resources. In the initial stages of project development, however, little may be known about the nature and magnitude of such complexity. This paper aims to ensure that this gap is at least subjectively assessed and addressed. Design/methodology/approach: Research, using focus group workshops with a convenience sample of construction professionals, was carried out to test the validity of a Project Early Stage Complexity Assessment Tool (PESCAT). The PESCAT concept brings together selected complexity theories and uses subjectively based measures for assessment. Findings: The findings confirm that an early-stage project complexity assessment tool is practicable and can contribute to project management practice in the construction industry. It should be applied by individual project stakeholders using small teams of experienced staff. PESCAT explores project complexity through "filter" sets of perspective factors which should be customised to reflect the stakeholder's role and processes in a project. Originality/value: In the initial complexity assessment model, resolution space and uncertainty were tested as project complexity parameters. However, in subsequent versions of the tool, four measures (differentiation and differentiation uncertainty; interdependency and interdependency uncertainty) are used in an innovative way that focuses users' attention more clearly and points to a more targeted approach for addressing project complexity. The value of our model lies in its practical application and the project management benefits it can deliver.